Peningkatan Hasil Belajar IPS Melalui Model Pembelajaran Quantum Teaching Pada Siswa Kelas V UPT SPF SD Negeri 178 Tulekko Kab. Bulukumba - Nirwana Talle; Hidayah Quraisy; Syarifah Aeni Rahman (LPPM Politeknik Pratama, 2024)
This type of research is classroom action research (PTK) which was carried out in two cycles. This research discusses improving social studies learning outcomes through the Quantum Teaching model for fifth grade UPT students at SD Negeri 178 Tulekko, Bulukumba Regency. The aim of this research is to obtain information on whether social studies learning outcomes improved after being taught through the Quantum Teaching model for class V students at UPT SD Negeri 178 Tulekko, Bulukumba Regency, to find out how students' activities during learning through the Quantum Teaching learning model for class V students at UPT SD Negeri 178 Tulekko Bulukumba Regency. The results of this research concluded that the application of the Quantum Teaching learning model could improve social studies learning outcomes with evidence of student activity in cycle I obtained a percentage of 61.66% and an increase in cycle II obtaining a percentage of 86.66%. Meanwhile, in cycle I, the percentage of learning outcomes was 55% with an average of 67 and in cycle II, the percentage of learning outcomes was 85% with an average of 78. So the increase in learning outcomes from cycle I to cycle II was 30%. So that the increase in test results shows that the indicators of success have been achieved.